Histone Deacetylase Inhibitor Modulates NKG2D Receptor Expression and Memory Phenotype of Human Gamma/Delta T Cells Upon Interaction With Tumor Cells - Bhat, Jaydeep; Dubin, Samuel; Dananberg, Alexandra; Quabius, Elgar Susanne; Fritsch, Juergen; Dowds, C. Marie; Saxena, Ankit; Chitadze, Guranda; Lettau, Marcus; Kabelitz, Dieter (Frontiers in Immunology, 2019)
The functional plasticity and anti-tumor potential of human γδ T cells have been widely studied. However, the epigenetic regulation of γδ T-cell/tumor cell interactions has been poorly investigated. In the present study, we show that treatment with the histone deacetylase inhibitor Valproic acid (VPA) significantly enhanced the expression and/or release of the NKG2D ligands MICA, MICB and ULBP-2, but not ULBP-1 in the pancreatic carcinoma cell line Panc89 and the prostate carcinoma cell line PC-3. Under in vitro tumor co-culture conditions, the expression of full length and the truncated form of the NKG2D receptor in γδ T cells was significantly downregulated. Furthermore, using a newly established flow cytometry-based method to analyze histone acetylation (H3K9ac) in γδ T cells, we showed constitutive H3K9aclow and inducible H3K9achigh expression in Vδ2 T cells. The detailed analysis of H3K9aclow Vδ2 T cells revealed a significant reversion of TEMRA to TEM phenotype during in vitro co-culture with pancreatic ductal adenocarcinoma cells. Our study uncovers novel mechanisms of how epigenetic modifiers modulate γδ T-cell differentiation during interaction with tumor cells. This information is important when considering combination therapy of VPA with the γδ T-cell-based immunotherapy for the treatment of certain types of cancer.